The Role of Defensins in HIV Pathogenesis. (3rd August 2017) - Pace, Barcley T.; Lackner, Andrew A.; Porter, Edith; Pahar, Bapi
Abstract : Profound loss of CD4 + T cells, progressive impairment of the immune system, inflammation, and sustained immune activation are the characteristics of human immunodeficiency virus-1 (HIV-1) infection. Innate immune responses respond immediately from the day of HIV infection, and a thorough understanding of the interaction between several innate immune cells and HIV-1 is essential to determine to what extent those cells play a crucial role in controlling HIV-1 in vivo . Defensins, divided into the three subfamilies α -, β -, and θ -defensins based on structure and disulfide linkages, comprise a critical component of the innate immune response and exhibit anti-HIV-1 activities and immunomodulatory capabilities. In humans, only α - and β -defensins are expressed in various tissues and have broad impacts on HIV-1 transmission, replication, and disease progression. θ -defensins have been identified as functional peptides in Old World monkeys, but not in humans. Instead, θ -defensins exist only as pseudogenes in humans, chimpanzees, and gorillas. The use of the synthetic θ -defensin peptide "retrocyclin" as an antiviral therapy was shown to be promising, and further research into the development of defensin-based HIV-1 therapeutics is needed. This review focuses on the role of defensins in HIV-1 pathogenesis and highlights future research efforts that warrant investigation.